Reaktualisasi Profesi Dakwah - Nurfuadi Nurfuadi (Komunika, 2016)
Mission profession is glory profession that becoming responsibility as mos/em believer, especially the mos/em scholars as prophet heir that is not easy to implemented. There is condition, rule cind criteria which must be fulfilled by the heir of this prophecy. As have done by Rasulullah, one of them is amanah (believe), fathonah (smart), and tabligh.